PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DALAM MENINGKATKAN MINAT DAN HASIL BELAJAR SEJARAH KEBUDAYAAN ISLAM DI MADRASAH IBTIDAIYAH NEGERI - Raudha Ningsih; Syaflin Halim; Abdul Halim Hanafi; Dasrizal Dahlan (SITTAH: Journal of Primary Education, 2022)
The learning results of Islamic Cultural History (SKI, Sejarah Kebudayaan Islam) for class VI MIN 6 students in Padang City showed unsatisfactory results. The reason is that students are less interested in the subject. Efforts to fix the problem are made by applying jigsaw-type cooperative learning. Through the experimental quasi-research method, this research aims to determine the influence of jigsaw-type cooperative models on student learning outcomes and interests in SKI subjects. The results of this study show that the jigsaw-type cooperative model affects student learning outcomes in SKI subjects. The sig value (2-tailed) post-test using the t-test is 0.000, which means it is smaller than > 0.05. It can be explained by the fact that jigsaw-type cooperative learning makes student learning outcomes positive and significantly correlated. Researchers also used evidentiary testing using the Anova test, which yielded a sig value, in addition to a t-test. (2-tailed) equal to 0.000. By using these criteria, it is proved that 0.000 < 0.05. In addition, it is known that the t-count value is 2.580 with a significant 0.05. The t-table count t value (1.84 0.05) and significant value is smaller because the table t value for df 29 is 2.179. (0.000 > 0.05).